Generic Integration of Lean, Agile, Resilient, and Green Practices in Automotive Supply Chain - Meysam MALEKI; Virgilio CRUZ MACHADO (Revista de Management Comparat International)
The purpose of this research is to development of a generic integrate approach for Lean, Agile, Resilient, and Green practices in automotive supply chain. A backward integration approach is followed starting from analyzing values of end customers through employing Bayesian network thereafter-qualitative correlations between supply chain practices and customer values are presented as the generic integration. Data about six customer values in automotive industry is presented and analyzed, and afterwards it is connected to supply chain practices resulting in the generic integration. Supply chain decision makers can benefit from this research in employing appropriate practices. In addition, this research contributes to marketing scholars in automotive industry by providing analysis of empirical data.